2019
DOI: 10.3390/ijms20040882
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of SiO2 Nanoparticles by Zebrafish Embryo Toxicity Test

Abstract: As the use of nanoparticles (NPs) is increasing, the potential toxicity and behavior of NPs in living systems need to be better understood. Our goal was to evaluate the developmental toxicity and bio-distribution of two different sizes of fluorescently-labeled SiO2 NPs, 25 and 115 nm, with neutral surface charge or with different surface functionalization, rendering them positively or negatively charged, in order to predict the effect of NPs in humans. We performed a zebrafish embryo toxicity test (ZFET) by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Five to 15% of zebrafish embryos did not show detachment of their tails and lacked a visible heartbeat. No differences in toxicity parameters were observed for PHB nanoparticles between the chorion-protected life stages before 48 h of development and hatched embryos until 96 h. Such a protective role of the chorion and toxicity differences is often observed for nanoparticles, e.g., described for SiO 2 nanoparticles [ 56 ]. In contrast to the observed toxicity on zebrafish embryos, PHB is described as a non-toxic biopolymer [ 57 ], and PHB films such as poly(3-hydroxyoctanoate) (PHO) were not toxic on L929 cells and not pro-inflammatory [ 58 ].…”
Section: Resultsmentioning
confidence: 93%
“…Five to 15% of zebrafish embryos did not show detachment of their tails and lacked a visible heartbeat. No differences in toxicity parameters were observed for PHB nanoparticles between the chorion-protected life stages before 48 h of development and hatched embryos until 96 h. Such a protective role of the chorion and toxicity differences is often observed for nanoparticles, e.g., described for SiO 2 nanoparticles [ 56 ]. In contrast to the observed toxicity on zebrafish embryos, PHB is described as a non-toxic biopolymer [ 57 ], and PHB films such as poly(3-hydroxyoctanoate) (PHO) were not toxic on L929 cells and not pro-inflammatory [ 58 ].…”
Section: Resultsmentioning
confidence: 93%
“…58,59 Therefore, in the current work, zebrafish embryos were used to validate the toxicity profiles of the NP library evaluated in the in vitro tests. Because some NPs are trapped by the chorion of zebrafish, 60 we have removed it to perform the screening. Our results showed that 18 NP formulations had an impact in the angiogenesis of the intersegmental vessels of zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Also, BSiO 2 #THY induced the same significant sublethal effects of thymol (pericardial edema, delayed yolk sac absorption, and delayed hatching) after 96 h of exposure (Figure 3 and Table 1). It is worth mentioning that the early stages of the zebrafish are protected by 2 outer protein membranes of 10 μm thickness (chorion and inner perivitelline membrane; Scholz et al 2008; Kais et al 2013; Li et al 2014; Vranic et al 2019), but the chorion contains pores with an average diameter of 0.5 to 0.7 μm, which could allow the passage of solute such as NPs (Ali et al 2017). In the present study, the BSiO 2 carrier did not aggregate and precipitate in the zebrafish medium, as occurred in the A. salina medium (Figure 5).…”
Section: Discussionmentioning
confidence: 99%